Pretreatment Of Oil Palm Fronds Using A Solvent-Ionic Liquid (BMIM)Cl To Enhance Glucose Recovery - Tan, Hui Teng (2011)
The potential of oil palm frond (OPF) as glucose source for fuel ethanol production was investigated in this current work. Pretreatment of lignocellulosic feedstock with a solvent, ionic liquid (IL) 1-butyl-3 methylimidazolium chloride ((BMIM)Cl) was used to facilitate the conversion of OPF into fermentable sugar (glucose). The pretreatment was accomplished by first subjecting OPF to ionic liquid treatment, followed by regeneration of cellulose using an anti-solvent. The effects of several pretreatment variables, such as temperature, retention time and solid loading on the biomass composition, crystallinity as well as its digestibility by enzyme and glucose recovery after pretreatment were studied.